Tingkat Pengetahuan Ibu Hamil Tentang HIV AIDS - Darlis, Idhar; Khasanah, Uswatun; Badaruddin, Asrianti (An Idea Nursing Journal, 2022)
2-3 pregnant women with HIV positive in developing countries do not have access to treatment to prevent HIV transmission. This results in 370,000 new HIV cases among infants each year. Of the approximately 1.5 million pregnant women who are HIV positive each year in developing countries. Efforts to give formula milk to newborns are mostly inappropriate because of the non-compliance of pregnant women with HIV, so they do not succeed in preventing Mother Transmission to Child Transmission (MTCT). The type of research used is quantitative research with a descriptive design. This research was conducted in the working area of ??the Teppo Health Center, Patampanua District, Pinrang Regency with a total of 30 respondents. This study aims to see the level of knowledge of pregnant women about HIV/AIDS. The results showed that respondents who had a sufficient level of knowledge were 17 people with a percentage (56.7%) and respondents who had a low level of knowledge were 13 people with a percentage (43.3%). From the results of this study, it can be seen that almost of the pregnant women who conduct examinations at the puskesmas there are still those who have less knowledge about the transmission of HIV/AIDS.